The Carbothermic Route to Magnesium - Hasan, Nurul (2006)
The carbothermic reduction of magnesia to produce magnesium offers the potential of a lower energy and higher productivity route for metal production compared to existing industrial routes. The reaction of magnesia and carbon produces a magnesium and carbon monoxide vapor. Slow cooling of that vapor will allow the reaction to quickly revert and the prevention of this reversion reaction is a major technical challenge. Two main approaches can be taken to prevent reversion and allow recovery of the metal product: rapid quenching of the vapor and dissolving the magnesium directly in a suitable metal solvent before reversion can occur. The commercial viability of either carbothermic route to magnesium is closely connected to the physical chemistry of each system.